Harnessing the interaction between redox signaling and senescence to restrain tumor drug resistance - Wu, Hao; Yu, Yang; He, Xiangning; Gong, Yanju; Huang, Jianqing; Wu, Peijie (Frontiers in Cell and Developmental Biology, 2025)
The persistent challenge of tumor drug resistance remains a critical issue in medical practice, particularly during anti-neoplastic therapies, where the plasticity of the tumor microenvironment (TME) significantly complicates clinical treatment. Cellular senescence, an irreversible and permanent arrest of the cell cycle, has been implicated in various vital physiological and pathological processes. However, increasing evidence suggests that senescent cells arising in the tumor microenvironment have emerged as key contributors to tumor drug resistance, primarily through a highly active secretome termed the senescence-associated secretory phenotype (SASP), which includes growth factors, chemokines, cytokines, and stromal metalloproteinases. These SASP secretions significantly reshape the TME, enabling cancer cells to evade immune destruction. Interestingly, redox signaling networks are deeply intertwined with the cellular senescence process, influencing tumor progression and therapeutic outcomes. These studies highlight the complexity and heterogeneity of cellular senescence and redox signaling in diverse cancers. Notably, characterizing the heterogeneity of senescent cell populations in the context of drug resistance could facilitate the identification of key signaling nodes. Therefore, a thorough comprehension of the adaptive interactions between redox signaling and senescence across various tumor stages and cell subsets may reveal novel therapeutic targets. In this review, we will interpret the role of redox signaling in driving senescence and its regulation of SASP secretion in TME. Additionally, we will provide insights into existing and emerging clinical interventions that harness redox modulation to improve therapeutic efficacy while minimizing adverse effects. Together, co-targeting tumor cells and senescent counterparts in the tumor microenvironment may provide the potential to achieve enhanced therapeutic benefits and restrain tumor relapse in future clinical oncology.